AB0804 OSTEOARTHRITIS (OA) PATIENTS WITH LOW BASELINE MULTIDIMENSIONAL HEALTH ASSESSMENT QUESTIONNAIRE/ROUTINE ASSESSMENT OF PATIENT INDEX DATA (MDHAQ/RAPID3) SCORES FOR PAIN, PATIENT GLOBAL ASSESSMENT AND MORNING STIFFNESS ARE SIGNIFICANTLY MORE LIKELY TO IMPROVE OVER THE NEXT 6 MONTHS. (June 2019) - Castrejon, Isabel; Riad, Mariam; Block, Joel; Pincus, Theodore
Abstract : Background: The course of osteoarthritis (OA) is highly variable; up to 50% of patients show little progression over many years, while other patients show rapid progression. Relatively little is known about the clinical variables that might affect prognosis for progression. Objectives: To analyze OA patient status in routine care at baseline according to baseline candidate prognostic multidimensional health assessment questionnaire (MDHAQ) variables, and 6 months later as improved, worsened or similar according to the same variables. Methods: All patients complete an MDHAQ/RAPID3 (routine assessment of patient index data) at all visits prior to seeing the rheumatologist at an academic site. The 2-page MDHAQ/RAPID3 includes 0-10 scores for physical function (FN), and visual analog scales (VAS) for pain (PN) and patient global assessment (PATGL), compiled into a 0-30 RAPID3, as well as a 0-10 fatigue VAS, 0-48 self-report painful joint count, 0-60 symptom checklist, and minutes of morning stiffness. OA patients were classified into 3 groups, based on change in RAPID3 ≥3.8, the minimal clinically important improvement (MCII), from baseline to 6-month follow-up (range 3-9 months), as >3.8, <3.8, or within 3.8 units. Statistical significance was studied with one-way analysis of variance (ANOVA) and chi square. Results: Among 173 OA patients, 22 (13%) were improved, 95 (55%) unchanged, and 56 (32%) worsened 6 months later. The 3 groups did not differ significantly in age, gender, ethnicity, educational level or BMI (Table). Patients who improved compared to those who were unchanged or worsened had significantly lower baseline RAPID3, pain and patient global VAS, and morning stiffness. The patients who improved also had lower, but not statistically significant, physical function score and fatigue VAS. No differences were seen among the 3 groups in numbers of symptoms or self-report painful joint counts (Table). Conclusion: OA patients who were improved over 6 months according to RAPID3 had significantly lower baseline scores for RAPID3, pain, patient global assessment, and morning stiffness. It may be of value to stratify patients in clinical trials, other clinical research, and routine clinical care according to these variables. Disclosure of Interests: None declared